Emerging technologies in information systems project management - Choquehuanca-Sánchez, Ana María; Kuzimoto-Saldaña, Keiko Donna; Muñoz-Huanca, Jhonatan Rubén; Requena-Manrique, Dennis Gerardo; Trejo-Lozano, Rodrigo Antony; Vasquez-Martinez, Josemaria Isimer; Zenozain-Gara, Edy Guillermo; Marín Rodriguez, William Joel (EAI Endorsed Transactions on Scalable Information Systems, 2024)
The article discusses emerging technologies in information systems project management. Project management is a modern discipline that began to take shape from 1900 and has evolved and adapted to the needs of society and business. Emerging technologies such as artificial intelligence, blockchain, augmented and virtual reality, and process automation are transforming the way information systems projects are managed. These technologies can be used to analyze large amounts of data, ensure data integrity and security, visualize a project's design and perform virtual testing, and automate tasks to reduce project time and cost. It is important for companies to be aware of these technologies and use them effectively to improve the efficiency and profitability of their projects.
Keywords: artificial intelligence; blockchain; process automation; paradigm shift; systems integration